F63 Validation of fitbit charge 4 for sleep monitoring in participants with Huntington's disease. (12th September 2022) - Renerts, Klavs; Doheny, Emer P.; Baumann, Christian; Werth, Esther; Baumgartner, Philipp; Busse, Monica; Jung, Hans H.; Lowery, Madeleine M.; ,
Abstract : Background: Wearable devices enable long-term home sleep monitoring, allowing changes in sleep quality and sleep patterns to be examined in Huntington's Disease (HD). Aim: To establish the accuracy of Fitbit Charge 4 sleep metrics and heart rate during sleep compared to polysomnography (PSG) in participants with HD. Methods: Ten participants with HD (Unified HD Rating Scale motor scores 5-51 points) wore a Fitbit Charge 4 during overnight PSG. PSG sleep stages were scored by an expert sleep physiologist. Fitbit sleep stages (8 participants; 30s epochs), and Fitbit heart rate data (all participants; 60s epochs) were extracted. Total sleep time, total wake time, time in each sleep stage (REM, Light and Deep) were calculated using sleep staging data. Sleep fragmentation index was calculated as number of awakenings per hour. The mean and coefficient of variation in heart rate were calculated for each sleep. Agreement was assessed using Bland Altman plots, and the sensitivity and specificity of Fitbit to each sleep stage were calculated. Results: Compared to PSG, Fitbit ( Figure 1 ) overestimated total sleep time by 5±26.8 mins and REM sleep by 5.21±22.35 mins, and underestimated deep sleep by 4.1±21.8 mins. Fitbit sensitivity and specificity to sleep was 90% and 73%, REM was 76% and 96%, and deep sleep was 54% and 94%. Heart rate during sleep was estimated by Fitbit with a mean error of -0.32±0.54 bpm compared with PSG. Conclusions: Preliminary results suggest that Fitbit Charge 4 may be suitable to monitor sleep stages and heart rate during sleep in HD.